Investigating hydrodynamic cavitation as an efficient means for removal of per- and polyfluoroalkyl substances from solution - Kabiri S; Jafarian M; Navarro DA; Whitby CP; McLaughlin MJ (Elsevier BV, 2024)
With nearly five decades of per- and polyfluoroalkyl substances (PFASs) being associated with firefighting and industrial activities, these compounds inevitably accumulate in both ground and surface water. PFAS contamination in water has emerged as a significant environmental and public health concern, particularly perfluorooctanesulfonic acid (PFOS), which is often found in higher concentrations compared to other PFAS and has more pronounced adverse health effects. Addressing PFAS contamination requires treating large volumes of water, making technologies that rapidly separate and concentrate PFASs highly favoured. The strong surface activity of PFAS, such as PFOS, enables them to generate colloidal gas aphrons (CGAs) during high shear mixing of their aqueous solutions, where PFASs can be separated and collected as foam. This study aims to evaluate the effectiveness of high shear mixing in separating PFOS from solution, leveraging its accumulation at air–water interfaces. High shear-assisted PFOS separation was tested by varying parameters like rotational speed (4000 to 10,000 rpm), mixing time (30 s to 30 min), and the effect of electrolytes. Results showed greater PFOS separation in the presence of electrolytes, particularly monovalent cations like Na+, compared to divalent cations such as Ca2+, due to the creation of more stable CGAs with smaller sizes. At a mixing rate of 6000 rpm, 85 % of PFOS was removed in 30 s from a highly contaminated PFOS solution (10 mg/L), with over 95 % separation after 5 mixing cycles. While high-shear mixing was efficient in PFOS separation from highly contaminated solutions it was less efficient for low-level contaminated solutions (less than 1 mg/L). These results suggest that hydrodynamic cavitation induced by high-shear mixing seems promising for enhancing the separation of PFOS from heavily contaminated solutions. This technique could serve as a standalone method or be integrated with other PFAS removal technologies to enhance the overall efficiency of PFAS removal from polluted water sources.
Keywords: Per- and polyfluoroalkyl substances; PFASs; Separation; Foam; Colloidal gas aphrones; High shear